Syntactic Analysis of Donald Trump’s Inaugural Speech - Olusegun Oladele Jegede (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This study aimed at examining the syntactic devices in the inaugural speech of Donald Trump. The study adopted a quantitative and qualitative method. The study used frequencies and statistics to examine the frequency of occurrence of the syntactic devices used in the speech. The study also focused on how the devices helped in the interpretation of the speech. The speech was critically read. The syntactic devices (sentence types, modality, conjunctions, adverbials and pronouns) used in the speech were identified, categorised, interpreted and discussed according to the ideas presented in the speech. The findings revealed that the types of sentences employed were simple, complex, and compound sentences. He used more of simple sentences to achieve succinctness in his speech. He also used syntactic devices such as modal verbs, conjunctions, personal pronouns and adverbial phrases to accomplish conciseness, logicality, accuracy and effectiveness in his speech. The study concluded that the use of syntactic devices helped the speaker to achieve cohesion in the speech, thereby enabling him to express his motives, plans, feelings, and expectations from the Americans.